Cortical Pressure Injury: A Hypothesis to Explain the Incongruity of Clinical and Radiologic Improvement in Decompressive Craniectomy - Sudip Kumar Sengupta; Harjinder Singh Bhatoe (Indian Journal of Neurosurgery)
It has astonished neuroscientists since the advent of decompressive craniectomy as to why a seemingly successfully achieved goal of reduction in intracranial pressure (ICP), by removing a portion of the cranial vault and the resultant intracranial volume augmentation, fails to give the desired beneficial clinical outcome in every case and in fact, at times, proves to be deleterious in some conditions with a shared problem of refractory raised ICP. The authors propose a hypothesis based on the understanding of the anatomy and physiology of the brain that can explain the fallacy.